Effect of electromagnetic field radiation on transcriptomic profile and DNA methylation level in pig conceptuses during the peri-implantation period - Anita Franczak; Agata Zmijewska; Ewa Monika Drzewiecka; Wiktoria Kozlowska; Pawel Wydorski; Lukasz Paukszto; Tiziana L. Brevini (Scientific Reports)
Abstract Extremely low-frequency electromagnetic field (ELF-EMF) radiation alters the steroidogenic activity of porcine conceptuses during the peri-implantation period. This study investigated whether short exposure (2 h) to ELF-EMF radiation may induce changes in the transcriptomic profile of conceptuses and their DNA methylation levels, with a focus on the promoter regions of differentially expressed genes of interest. Porcine conceptuses were collected on days 15–16 of pregnancy, preincubated, and then exposed in vitro to ELF-EMF at a frequency of 50 Hz. ELF-EMF treatment affected the expression of 21 protein-coding transcripts, including solute carrier family 34 member 1 (SLC34A1), hydroxysteroid 17-beta dehydrogenase 2 (HSD17B2), apolipoprotein M (APOM), regucalcin (RGN), heat shock protein family A (Hsp70) member 6 (HSPA6), fibrinogen beta chain, and fibrinogen gamma chain (FGG). There were evaluated 21 GO annotations for biological process terms, nine GO annotations for cellular component terms and two KEGG pathways. The ELF-EMF exposure increased approximately 16 times genomic DNA methylation in conceptuses. ELF-EMF-induced changes in methylation were observed in the promoter regions of APOM, HSD17B2, FGG, and SLC34A1. The results determined 116 predicted single nucleotide variant substitutions within RNA editing sites. In conclusion, ELF-EMF radiation appears to interact with DNA methylation levels and to affect the expression of genes involved mainly in cellular homeostasis, conceptuses development, and attachment, suggesting the need for further investigation to elucidate better the impact of ELF-EMF exposure on the physiology of early conceptuses.